PENGARUH METODE BERCERITA MELALUI MEDIA GAMBAR TERHADAP PERKEMBANGAN BAHASA ANAK USIA PRASEKOLAH TK AISYIYAH BUSTANUL ATHFAL 1 GEMPOL PASURUAN - Ratnaningsih, Tri; Erdyan Romadeni putri, Ellsyana (JURNAL KEPERAWATAN BINA SEHAT, 2014)
The establishment of language ability is the basic capabilities that need to be developed in kindergarten, one aspect of which is developed in the kindergarten language proficiency in children. Developing language skills in children need to use methods – methods, one of a kind that method is by the method of storytelling. This research aims to prove the influence of method of telling stories through media images of language development in preschool-aged children parsekolah Aisyiyah Bustanul Athfal 1 Gempol Pasuruan. On the research design used was the experiment with the approach pre quasy-test post test control group design. Samplingnya use Non Probability Sampling with the total sampling techniques. The sample used 66 students, the intervention group students awarded 33 method of storytelling through the medium of the image with the retelling of stories submitted, whereas 33 students in the control group given method tells the story through the medium of an image without retelling the story presented. Its independent variable method of storytelling through the medium of images and variable dependennya language development of preschool-aged children. The Data collected using the DDST (denver development screening test II) before and after the given method of telling stories through pictures. The results of the croostab (cross-tabulations) note that an increase in language development in preschool-aged children in the intervention group and the control group. Storytelling activities with the media so the image can increase childrens language proficiency with the ability to express language, be able to understand the language, and literacy.Key words: Method of storytelling, Language development, Preschool age children